Assessing the Capability of E-Attendance Systems in Local Government Institutions Using COBIT 2019: A Case from Indonesia - Andysah Putera Utama Siahaan; Efriansyah Putra Bahari Barus; Muhammad Hasanuddin; Zulfan Zulfan; Fakhri Rizaldi (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
This research evaluates the capability level of the E-Attendance system at the General Bureau of the Regional Secretariat of North Sumatra Province using the COBIT 2019 framework. A mixed-method approach was employed, integrating document analysis, interviews, questionnaires, and system log reviews to assess four key governance and management objectives: DSS06 (Manage Business Process Controls), APO13 (Managed Security), APO14 (Managed Data), and MEA01 (Performance and Conformance Monitoring). The results indicate that the current capability levels range between Level 1 (Performed) and Level 2 (Managed), reflecting partially implemented and inconsistently standardized governance practices. Based on organizational policies, regulatory requirements, and operational needs, the target capability level for all assessed domains is defined at Level 3 (Established), where processes are formally documented, standardized, and consistently implemented across organizational units. The gap analysis reveals deficiencies in data governance structures, security control enforcement, and performance monitoring mechanisms. Nevertheless, the findings demonstrate that improvements in process capability significantly enhance data quality dimensions, including completeness, accuracy, consistency, and timeliness. This study contributes to public sector IT governance literature by providing an evidence-based COBIT 2019 capability assessment and proposing a structured improvement roadmap to achieve the defined target capability level and strengthen digital governance maturity.